Cranioencephalic functional lymphoid units in glioblastoma - Dobersalske, Celia Christina; Rauschenbach, Laurèl; Hua, Yichao; Berliner, Christoph; Steinbach, Anita; Grüneboom, Anika; Kokkaliaris, Konstantinos D.; Heiland, Dieter H.; Berger, Pia; Langer, Sarah; Tan, Chin Leng; Stenzel, Martin; et al. (Nature medicine, 2024)
The ecosystem of brain tumors is considered immunosuppressed, but our current knowledge may be incomplete. Here we analyzed clinical cell and tissue specimens derived from patients presenting with glioblastoma or nonmalignant intracranial disease to report that the cranial bone (CB) marrow, in juxtaposition to treatment-naive glioblastoma tumors, harbors active lymphoid populations at the time of initial diagnosis. Clinical and anatomical imaging, single-cell molecular and immune cell profiling and quantification of tumor reactivity identified CD8+ T cell clonotypes in the CB that were also found in the tumor. These were characterized by acute and durable antitumor response rooted in the entire T cell developmental spectrum. In contrast to distal bone marrow, the CB niche proximal to the tumor showed increased frequencies of tumor-reactive CD8+ effector types expressing the lymphoid egress marker S1PR1. In line with this, cranial enhancement of CXCR4 radiolabel may serve as a surrogate marker indicating focal association with improved progression-free survival. The data of this study advocate preservation and further exploitation of these cranioencephalic units for the clinical care of glioblastoma.